A review of the genus Ruidocollaris Liu (Orthoptera: Tettigoniidae), with description of six new species from China - Liu, Chun-Xiang; Kang, Le (Zootaxa, 2010)
The validity of Ruidocollaris Liu is re-confirmed based on abundant material from China. A review on Ruidocollaris in the world is given, with a list of nine species. Characters of the stridulatory file on the underside of the male left tegmen, and male stridulatory area on left and right tegmen are provided for each species. Six new species are described, including R. rubescens sp. nov., R. longicaudalis sp. nov., R. apennis sp. nov., R. latilobalis sp. nov., R. ferruginescens sp. nov., and R. parapennis sp. nov.. A key to nine species of the genus Ruidocollaris is provided accompanied by illustrations. Distribution maps of Ruidocollaris species, mainly from China, are provided.